2.4 GHz wireless sensor network for smart electronic shirts - Carmo, J. P. (2005)
This paper presents a wireless sensor network for smart electronic shirts. This allows the monitoring of individual biomedical data, such the cardio-respiratory function. The solution chosen to transmit the body’s measured signals for further processing was the use of a wireless link, working at the 2.4 GHz ISM band. A radio frequency transceiver chip was designed in a UMC RF 0.18 µm CMOS process. The power supply of the transceiver is 1.8 V. Simulations show a power consumption of 12.9 mW. Innovative topics concerning efficient power management was taken into account during the design of the transceiver.